TRANSFORMASI MODERASI BERAGAMA MELALUI KEGIATAN KOLOMAN SEBAGAI MEDIA PENDIDIKAN ISLAM DI KELURAHAN LAWANGAN DAYA PADEMAWU PAMEKASAN - Ach. Sayyi; Imaniyatul Fithriyah (LPPM STAI Muhammadiyah Probolinggo, 2025)
Koloman, as a religious tradition in Lawangan Daya Village, continues to be practiced conventionally and has not yet been optimal in instilling the values of religious moderation, resulting in vulnerability to exclusive views and limited understanding of tolerance and anti-extremism among the community. This community engagement project aimed to transform Koloman into a contextual Islamic educational medium, emphasizing the strengthening of understanding and the formation of moderate attitudes at the community level. The method applied involved participatory empowerment through dialogue, thematic discussions, creative training, and evaluation based on observation and pre-post tests with Koloman participants as the main subjects. The results demonstrate a significant increase in the understanding of religious moderation, more active participation among vulnerable groups, and the development of social networks between congregations which support the sustainability of moderation practices. This program proves that local traditions can be effective instruments in shaping a peaceful and inclusive community character.